Differential diagnosis of axial spondyloarthritis and psoriatic arthritis with axial involvement - E. E. Gubar; T. V. Korotaeva; T. V. Dubinina; Yu. L. Korsakova; E. Yu. Loginova; L. D. Vorobyeva; P. O. Tremaskina; E. M. Agafonova; K. V. Sakharova; A. O. Sablina; A. V. Smirnov; Sh. F. Erdes; et al. (Современная ревматология)
Objective: To analyze clinical and imaging characteristics of patients with axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA) with spinal involvement (axial PsA, axPsA) and to develop principles for the differential diagnosis between axPsA and axSpA.Material and methods. A total of 222 patients were examined: 108 with axSpA (Group 1) and 114 with axPsA (Group 2). Group 1 included patients meeting the criteria for axSpA/ankylosing spondylitis (AS); Group 2 included patients meeting the CASPAR criteria for PsA with axial involvement. Axial involvement was defined as radiographically confirmed (rc) sacroiliitis (SI; bilateral SI ≥ grade II or unilateral SI ≥ grade III), active SI on MRI, or ≥1 syndesmophyte in the cervical (CS) and/or lumbar (LS) spine. Inflammatory back pain (IBP) was assessed using ASAS criteria.Results and discussion. Patients in Group 1 were younger (p<0.001), more frequently HLA-B27 positive (p<0.001), and more often had IBP (p=0.001). In Group 2, later onset of back pain (>40 years) was more common (p<0.001), along with peripheral arthritis (p<0.001), dactylitis (p=0.004), and skin psoriasis (p<0.001). Nail psoriasis was observed exclusively in Group 2 (p<0.001). Heel enthesitis was more frequent in Group 1 (p<0.001). Patients in Group 2 had higher BASDAI scores (p<0.001) and more often had high ASDAS-CRP disease activity (p<0.001). They also had higher BASFI scores (p=0.008), pain scores (p=0.002), and patient global assessment (p=0.021).rcSI and sacroiliac joint ankylosis were more common in Group 1 (p=0.03 and p=0.006, respectevly). Group 2 more frequently exhibited syndesmophytes in the LS (p<0.001) and CS (p=0.004), as well as bulky (p<0.001), asymmetric (p=0.006), and non-bridging (p<0.001) syndesmophytes. Vertebral changes in the absence of SI (p<0.001), higher mSASSS scores (p<0.001), and more frequent erosions of hand and foot joints, multiple erosions, osteolysis, juxta-articular new bone formation (p<0.001 for all), and joint ankylosis (p=0.008) were also observed in Group 2, along with elevated CRP levels (p=0.002).Conclusion: This study revealed several genetic, demographic, clinical, and imaging differences that collectively enable the differential diagnosis between axSpA/AS and axPsA.